'Are we wasting our time?': bushfire practitioners and flammable futures in northern Australia. (19th May 2018) - Neale, Timothy
Abstract: Humans are 'fire creatures' that have used fire for millennia to shape local environments to diverse purposes. Our capacity for combustion has also forced global climatic changes and rendered the planet increasingly flammable, creating the conditions for progressively higher impact bushfires now and into the future. Meanwhile, governments in fire-prone countries such as Australia have continued to allow settlements to be established (and re-established) in wildland–urban interfaces. Like other 'natural hazards', bushfire is thereby a social phenomenon bound up with human values, practices and decisions. But, while studies of the social dimensions of 'natural hazards' are steadily rising, this scholarship has rarely addressed natural hazard management practitioners directly, precisely those authorised and entrusted to intervene in the distribution of hazard probabilities and consequences. This paper seeks to help remediate this research gap, illustrating how cultural, ecological, economic and political factors thoroughly condition hazard management and modes of intervention. Drawing on a case study in the Northern Territory's Greater Darwin region, this paper suggests not only that examining such sociocultural realities provides new insights into hazards and their distribution, but also that attention to such issues is crucial to understanding our flammable future in the Anthropocene.